The Importance of Creativity Towards Innovation with Digital Applications to Improve The Education of The Indonesian Millennial Generation - Budi Sulistiyo Nugroho; Rosmaniar Sembiring; B.M.A.S. Anaconda Bangkara; Endang Fatmawati; Rahma Dini Warastuti (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This article aims to look further at the creativity of university students in using technology. Technology is a tool that can be relied upon to assist students in working with assignments and other academic requirements. The study used secondary data searching from online literature. The literature and material were taken from books, scientific papers, and website material, national and international publications. The results indicate that the current students doing the assignments given by the lecturers cannot be separated from the help of technology, both in doing paper assignments and other tasks. For further research, it is hoped that these results will be in the form of a field at one of the universities in Indonesia, in a quantitative form so that there are how many percent of students are highly dependent on doing assignments by relying on the internet availability.